Are stationary hyperinflation paths learnable? - Klaus Adam; George W. Evans; Seppo Honkapohja (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
Earlier studies of the seigniorage inflation model have found that the high-inflation steady state is not stable under adaptive learning. We reconsider this issue and analyze the full set of solutions for the linearized model. Our main focus is on stationary hyperinflationary paths near the high-inflation steady state. The hyperinflationary paths are stable under learning if agents can utilize contemporaneous data. However, in an economy populated by a mixture of agents, some of whom only have access to lagged data, stable inflationary paths emerge only if the proportion of agents with access to contemporaneous data is sufficiently high.
urn:nbn:de:hebis:30-10663
Keywords: C62; D83; D84; E31; 330; Indeterminacy; inflation; stability of equilibria; seigniorage; Hyperinflation; Münzgewinn; Inflationserwartung; Lernprozess; Theorie; Hyperinflation; Münzgewinn; Inflationserwartung; Lernprozess; Theorie